2011
DOI: 10.1111/j.1471-0528.2011.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late epidural analgesia and the risk of instrumental delivery in nulliparous women

Abstract: rics, of 12 993 nulliparous women, showing that even use in the latent phase, compared with later, led to no difference. It was really very early compared with later, rather than late. There was a very high rate of intervention in both arms, but the rate of caesarean section was modest (23-24%), although not at our current common rates of up to or exceeding 30%. Wong et al. 6 reported on a second study by the same group, in which nulliparous women were again exposed to combined spinal and epidural analgesia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Labor analgesia in the latent phase has been recognized and accepted by anesthesiologists worldwide. [1][2][3][4][5] However, the exact dose of sufentanil with the combination of ropivcaine required to administer epidural analgesia in the early first stage of labor remains unclear. Even in the practice guideline for obstetric anesthesia of 2016, the reasonable use of opioids in epidural administration of labor analgesia was not mentioned, and only a low concentration of local anesthetics was recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Labor analgesia in the latent phase has been recognized and accepted by anesthesiologists worldwide. [1][2][3][4][5] However, the exact dose of sufentanil with the combination of ropivcaine required to administer epidural analgesia in the early first stage of labor remains unclear. Even in the practice guideline for obstetric anesthesia of 2016, the reasonable use of opioids in epidural administration of labor analgesia was not mentioned, and only a low concentration of local anesthetics was recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, meta‐analysis has been broadened to include nonrandomized trials and, increasingly, studies that come from different environments or other nonheterogeneous settings. It is in the context of these concerns that the meta‐analysis by Wassen et al will be assessed (2).…”
mentioning
confidence: 99%
“…Wassen et al have conducted a meta‐analysis of randomized controlled trials of women receiving epidural analgesia early versus later in labor (2). They concluded that the early use of epidural analgesia, before the active phase of labor, does not result in an increase in either instrumental delivery or cesarean section.…”
mentioning
confidence: 99%
See 1 more Smart Citation